Toward the integration of personality theory and decision theory in explaining economic behavior: An experimental investigation - Rustichini, Aldo; DeYoung, Colin G.; Anderson, Jon E.; Burks, Stephen V. (Journal of behavioral and experimental economics, 2016)
•We systematically assess the relationships between economic preferences and personality traits.•We analyze a large set of adult non–student subjects with data on several life outcomes.•Personality traits statistically predict outcomes as well or better than economic preferences.•Decision theory and personality variables are meaningfully statistically related.•Neuroticism and cognitive ability together explain much of risk preferences. Economics and trait-based personality psychology have taken different approaches to understanding individual differences. The former emphasizes variables measured according to formal decision theory; the latter instead emphasizes variables derived from the factor analysis of trait assessments. In a data set on trainee truckers in a large US company, we provide a systematic assessment of the empirical pattern of relationships and correlations between the measurements used in these two approaches by comparing the predictive power of variables derived from personality theory and decision theory for several individual characteristics and outcomes, and relating the two sets of measurements to each other. We show that personality traits have a comparable or stronger statistical predictive power than do economic preferences for several dependent variables, including credit score, job persistence, and heavy truck accidents. They also have strong predictive power for Body Mass Index (BMI) and smoking status. Further, decision theory and personality variables are meaningfully related. For example, we confirm that cognitive ability explains a substantial part of time preferences, and find that Neuroticism and cognitive ability together explain attitudes toward risk. In an experimental game, cognitive skills and Agreeableness explain important aspects of strategic behavior.